The National Bank of Economic and Social Development on the Brazilian Development Strategies: From Internal Articulation to Expansion to Latin America - Sousa Kraychete, Elsa; Carvalho Cristaldo, Rômulo (Geopolítica(s). Revista de estudios sobre espacio y poder, 2014)
This paper traces the role of the National Bank of Economic and Social Development ―BNDES― at two distinct moments in Brazil’s economic development trajectory. The first corresponds to the implementing of economic policies based on developmental ideals, when the Bank establishes itself as a funding institution and long-term credit offerer, thus becoming the main financer of State-coordinated infrastructure and industrial sectors of the Brazilian economy. The second one, when the Bank, following liberal inspired economic policy strategies which guide governmental actions, redirects its efforts towards establishing itself as the coordinator and financer of the Brazilian asset restructure by means of mergers and acquisitions promoted by privatizations. The ownership change, more than just a change in control from state-owned to private capital, also leads to a productive diversification of industrial groups, thus, empowering the production of commodities and the civil construction sector. In such scenario, the Bank redefines its relationships with national and foreign private capital, and its presence within South America as a financer of Brazilian exports.
Keywords: National Bank of Economic and Social Development; development; funding; Brazil; South America.